"It's often liberating": consumers discuss causal beliefs in the treatment process. (4th July 2019) - Larkings, Josephine S.; Brown, Patricia M.; Scholz, Brett
Abstract: Background : Causal beliefs are thought to influence consumers' perceptions of their mental illness and self-stigma, and may impact treatment and recovery. Understanding consumers' perspective on causes being addressed in treatment is vital to help guide future research and improve services. Aim : This study aimed to explore consumers' views on causes of mental illness being addressed in treatment, along with their subjective experiences of how causes were focused on in their treatment. Methods : Using a qualitative approach, semi-structured interviews were conducted with 23 consumers who self-identified as having a mental illness. A thematic analytic framework was used to identify and analyse themes that emerged within the data. Results : Consumers believed that causes were important and should be addressed in treatment, and identified several associated benefits including increased insight/personal understanding of their illness, symptom management and relapse prevention and reduced self-blame. Negative consequences and considerations were also identified. Conclusion : Causes help consumers make sense of their illness, and consumers would like causes to be addressed in treatment. More research is needed on how mental health professionals can address causes effectively as consumers are currently dissatisfied with how causes were discussed in their treatment.